Innovation of a Chest-Covering Coat “Pid Oak - Perd Jai” for In-patients Undergoing EKG Recording, Kham Cha-I Hospital, Mukdahan Province - จันปุ่ม, ปริชาติ; รัชอินทร์, ดรุณี (Journal of Health Science of Thailand, 2023)
Heart rate monitoring service in Kham Cha-i Hospital was performed in a hall with a normal curtain that did not have any privacy because there was no specific examination room. Therefore, service recipients had to reveal the upper part of the body. Many of them, especially female, felt embarrassed and inconvenient for the examination. Since an electrocardiogram test requires an upper part of the body be exposted for attaching the EKG leads, a square cloth is normally used to cover the exposted area, which is quite inconvenient, inappropriate and unattractive. In this regard, an innovation was made to reduce unneccessary exposure during EKG examination with the aim to reduce embarrassment and to protect the patient’s rights of privacy. The innovation was named: “Pid-Ok - Perd-Ji” (or covering the chest - opening the heart) to be used for patients undergoing electrocardiogram test. It was a gown with openings that were small enough to fit with the attachment of the EKG leads. This study was conducted to assess the opinion of patients and the medical staff performing the test. It was found that among 50 patients in the study, high level of satisfaction was observed. The EKG lead attachments were well functional. More over, the service providers were also satisfied with its use. Thus, the innovation was conviniently suitable for the test; and promotes the acceptance among patients requiring EKG service.was